A Homochiral Poly(2‐oxazoline)‐based Membrane for Efficient Enantioselective Separation. Issue 8 (18th January 2023) - Wang, Fanmengjing; Pizzi, David; Lu, Yizhihao; He, Kaiqiang; Thurecht, Kristofer J.; Hill, Matthew R.; Marriott, Philip J.; Banaszak Holl, Mark M.; Kempe, Kristian; Wang, Huanting
Abstract: Chiral separation membranes have shown great potential for the efficient separation of racemic mixtures into enantiopure components for many applications, such as in the food and pharmaceutical industries; however, scalable fabrication of membranes with both high enantioselectivity and flux remains a challenge. Herein, enantiopure S ‐poly(2, 4‐dimethyl‐2‐oxazoline) ( S ‐PdMeOx) macromonomers were synthesized and used to prepare a new type of enantioselective membrane consisting of a chiral S ‐PdMeOx network scaffolded by graphene oxide (GO) nanosheets. The S ‐PdMeOx‐based membrane showed a near‐quantitative enantiomeric excess ( ee ) (98.3±1.7 %) of S ‐(−)‐limonene over R ‐(+)‐limonene and a flux of 0.32 mmol m −2 h −1 . This work demonstrates the potential of homochiral poly(2, 4‐disubstituted‐2‐oxazoline)s in chiral discrimination and provides a new route to the development of highly efficient enantioselective membranes using synthetic homochiral polymer networks. Abstract : S ‐Poly(2, 4‐dimethyl‐2‐oxazoline)‐based membranes ( S ‐PdMeOx/GO) are prepared via a simple solution‐based method on porous substrates for chiral separation. The S ‐PdMeOx‐based network within the graphene oxide scaffold induced homochirality in the membrane. The resulting S ‐PdMeOx‐based membrane displays excellent enantioselectivity in separating racemic limonene mixtures.